2016
DOI: 10.5009/gnl15198
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Findings of Upper Gastrointestinal Involvement in Primary Vasculitis

Abstract: Background/AimsGastrointestinal involvement in vasculitis may result in life-threatening complications. However, its variable clinical presentations and endoscopic features, and the rarity of the disease, often result in delayed diagnosis.MethodsClinical characteristics, endoscopic features, and histopathological findings were reviewed from medical records.ResultsOf 6,477 patients with vasculitis, 148 were diagnosed as primary vasculitis with upper gastrointestinal involvement. Of these, 21 cases (14.2%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…However, mucosal biopsies can be essential to exclude other diseases, such as inflammatory bowel diseases. In the study by Gong et al ( 10 ), only 5.4% of the 124 biopsies taken from upper GI tract showed evidence of vasculitis. Zhang et al ( 12 ) analyzed endoscopic biopsies from 54 patients with HSP and gastrointestinal symptoms: all the biopsies demonstrated non-specific inflammation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, mucosal biopsies can be essential to exclude other diseases, such as inflammatory bowel diseases. In the study by Gong et al ( 10 ), only 5.4% of the 124 biopsies taken from upper GI tract showed evidence of vasculitis. Zhang et al ( 12 ) analyzed endoscopic biopsies from 54 patients with HSP and gastrointestinal symptoms: all the biopsies demonstrated non-specific inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies demonstrate the role of endoscopy in GI presentation of vasculitis. Gong et al ( 10 ) demonstrated the presence of erosion, petechiae, submucosal hemorrhage, or ulcers in 95.9% of the patients diagnosed as primary vasculitis with upper GI involvement, and the second portion of the duodenum was the most frequently involved site. The authors conclude that combining endoscopic findings with clinical and radiological features can facilitate diagnosis of vasculitis with upper GI tract involvement.…”
Section: Discussionmentioning
confidence: 99%
“…First, mucosal oedema, redness, erosions and ulcers were found localised to the duodenal and proximal jejunal mucosae, both of which are GI regions known to be involved in this condition. 11 Second, serum factor XIII activity was found to be markedly decreased, which is considered indicative of IgA vasculitis. 12 Third, massive infiltration of immune cells and mucosal haemorrhage were found in the jejunal biopsy specimens obtained during SBE.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, the detection rate of vasculitis in biopsy specimens is very low (5.4%). 11 IgA vasculitis lesions can occur anywhere throughout the length of the GI tract, but most patients have small intestinal lesions, including those affecting the duodenum. 9 Endoscopic findings in this disorder include redness, erosions, mucosal oedema, punctate bleeding, ulcers and purpura-like lesions…”
Section: Discussionmentioning
confidence: 99%
“…The small intestine, particularly the second portion of the duodenum, is the most frequently involved site (8). As the diagnostic yield of the endoscopic biopsy is low, the diagnosis of GI involvement of HSP depends on endoscopic findings and clinical features (9). Although the patient's skin biopsy exhibited leukoclastic vasculitis, analysis of the endoscopic biopsies of the duodenum and stomach was insufficient for a diagnosis of vasculitis.…”
Section: Discussionmentioning
confidence: 99%